2023
DOI: 10.3390/systems11060292
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Mixed Reality in Enhancing Student Learning Experience and Academic Performance: An Empirical Study

Abstract: In recent years, mixed reality (MR) technology has emerged as a promising tool in the field of education, offering immersive and interactive learning experiences for students. However, there is a need to comprehensively understand the impact of MR technology on students’ academic performance. This research aims to examine the effect of mixed reality technology in the educational setting and understand its role in enhancing the student’s academic performance through the student’s novel learning experiences and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Therefore, it is to the benefit of both students and instructors to provide learning opportunities that are both memorable and fruitful [ 1 ]. Therefore, Almufarreh [ 40 ] highlighted that the incorporation of interaction and fun in the learning process has the potential to greatly enhance the overall experience for both teachers and students. This, in turn, can directly contribute to increased satisfaction and improved academic achievement among students.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is to the benefit of both students and instructors to provide learning opportunities that are both memorable and fruitful [ 1 ]. Therefore, Almufarreh [ 40 ] highlighted that the incorporation of interaction and fun in the learning process has the potential to greatly enhance the overall experience for both teachers and students. This, in turn, can directly contribute to increased satisfaction and improved academic achievement among students.…”
Section: Discussionmentioning
confidence: 99%
“…the study also revealed that immersive virtual reality environment reduces cognitive loads among students. Almufarreh [47] explored the significance of mixed reality environment in fostering learning experience of students and their academic achievement by applying quantitative research design and revealed significant positive results in favour of mixed reality-based on experiential learning and interactivity. Sviridova et al [48] conducted an experimental study to gain understanding about immersive technologies as a medium to develop academic success and learning motivation of students studying in higher educational institutions and revealed effectiveness of immersive technologies at university level.…”
Section: Effectiveness Of Immersive Learning Environmentsmentioning
confidence: 99%